The Significance of Gender in Predicting the Cognitive Moral Development of Business Practitioners Using the Sociomoral Reflection Objective Measure - Kracher, Beverly (Journal of business ethics, 2008)
This study constitutes a contribution to the discussion about moral reasoning in business. Kohlberg’s (1971, in Cognitive Development and Epistemology (Academic Press, New York), 1976, in Moral Development and Behavior: Theory and Research and Social Issues (Holt, Rienhart and Winston, New York)) cognitive moral development (CMD) theory is one explanation of moral reasoning. One unresolved debate on the topic of CMD is the charge that Kohlbergian-type CMD theory is gender biased. This research puts forth the proposal that the issue may be elucidated by exposing an ambiguity in “gender” (Borna and White: 2003, Journal of Business Ethics 47, 89–99; Gentile: 1993, Psychological Science 4(2), 120–122; Unger: 1979, American Psychologist 34(11), 1085–1094). We use the Sociomoral Reflective Objective Measure (SROM) to measure CMD and the Bem Sex Role Inventory (BSRI) to measure gender as a psychosocial concept, rather than as a biological classification. The results of our study indicate that high femininity, measured as a psychosocial attribute, is associated with significantly lower Kohlbergian-type CMD scores among business practitioners. Sex moderates the effect of gender on CMD, but only indirectly. Our research also reveals that education plays a significant moderating role in the relationship between gender and moral reasoning. In addition, age has a significant direct effect on CMD scores of business practitioners.